Предмет: Алгебра,
автор: CDolphin
Решите данное уравнение
Приложения:
Ответы
Автор ответа:
0
x^3 + 7x^2 - 4x - 28 = 0
x^2*(x + 7) - 4(x + 7) = 0
(x + 7)(x^2 - 4) = 0
(x + 7)(x + 2)(x - 2) = 0
x1 = -7; x2 = -2; x3 = 2
x^2*(x + 7) - 4(x + 7) = 0
(x + 7)(x^2 - 4) = 0
(x + 7)(x + 2)(x - 2) = 0
x1 = -7; x2 = -2; x3 = 2
Автор ответа:
0
х^2(x+7)=4(x+7)
x^2=4
x=2 x=-2
x^2=4
x=2 x=-2
Похожие вопросы
Предмет: Математика,
автор: farzalinamaram
Предмет: Музыка,
автор: Аноним
Предмет: Русский язык,
автор: Sharifa16
Предмет: Химия,
автор: natalya0071
Предмет: Математика,
автор: fati001